La « mémoire indigène » dans le Mexique contemporain : de la relecture du passé colonial à l’utopie de la nation pluriculturelle - Miriam Hernández Reyna (Caravelle)
This paper examines the history of Mexico’s native memory concept. To achieve this, three memorial phases are rebuilt : first, the emergence of the colonial past’s review as a historical trauma ; next, how the native Latin-American and Mexican movements have taken ownership of this past’s meaning in order to define their identity as “ancestral victims” ; and finally, the phase of such recognition within the new cultural plurality’s rhetoric.